2017
DOI: 10.1111/ner.12567
|View full text |Cite
|
Sign up to set email alerts
|

Explantation Rates and Healthcare Resource Utilization in Spinal Cord Stimulation

Abstract: OBJECTIVES Certain patients ultimately undergo explantation of their spinal cord stimulation (SCS) devices. Understanding the predictors and rates of SCS explantation has important implications for healthcare resource utilization (HCRU) and pain management. The present study identifies explant predictors and discerns differences in HCRU for at-risk populations. METHODS We designed a large, retrospective analysis using the Truven MarketScan Database. We included all adult patients who underwent a SCS trial fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Literature reviews have reported a rate of SCS system removal as high as 23.5% . One analysis of a more than five‐year span from 2007 to 2012 revealed a lower 9.2% explant rate . Recent reviews of explant data also examined the potential reasons for device explantation.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews have reported a rate of SCS system removal as high as 23.5% . One analysis of a more than five‐year span from 2007 to 2012 revealed a lower 9.2% explant rate . Recent reviews of explant data also examined the potential reasons for device explantation.…”
Section: Introductionmentioning
confidence: 99%
“…With explantation rates due to loss of efficacy remaining high for patients with tonic SCS-around 9.2% in one U.S. nationwide study of 8,727 tonic SCS patients 44 -the potential for SCS salvage in these patients is promising. Rates of tolerance are relatively high with traditional tonic SCS for the treatment of chronic pain, with one 10-year study reporting a 29% tolerance rate.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, if a paddle lead is no longer effective, a revision surgery is performed to place a new paddle, which may increase the risks of abandonment technology and perioperative complications, increased treatment costs, and potential worsening of the patient's overall pain level [4][5][6]. This case describes a 58-year-old woman with a history multiple lower back surgeries who was originally implanted with an 8-electrode (4 9 2) paddle lead via a T11 laminectomy spanning the T10-T11 vertebrae.…”
Section: Key Findingsmentioning
confidence: 99%